Donkey whey proteins ameliorate dextran sulfate sodium-induced ulcerative colitis in mice by downregulating the S100A8-TRAF6-NF-κB axis-mediated inflammatory response - Mohan Li; Qilong Li; Rayhnigul Abdlla; Jiali Chen; Xiqing Yue; Siew Young Quek (Food Science and Human Wellness)
Donkey milk has a variety of physiological functions, including antibacterial and anti-inflammatory. Donkey whey proteins (DWPs), as the main functional component in donkey milk, its inhibitory effect on colitis is still unclear. In this study, the inhibitory effect and potential mechanism of DWPs on dextran sulfate sodium (DSS)-induced colitis were investigated. Firstly, the DWPs and bovine milk whey proteins (BWPs) were characterized using proteomics. Then, we administered DWPs and BWPs to mice with colitis via oral gavage. The results of immunohistochemistry and flow cytometry indicated that DWPs increased T regulatory cell accumulation and increased the abundance of the cluster of differentiation 205+ (CD205+) macrophages compared to those with BWPs and in model groups. In addition, DWPs exhibited a more remarkable ability to inhibit pro-inflammatory proteins (S100A8, TRAF6, and NF-κB) expression and inflammatory secretion than BWPs. In addition, DWPs significantly decreased NF-κB and CD86 levels more than BWPs or the negative control in both LPS-stimulated human peripheral blood mononuclear cells or cell lines. These findings indicate that DWPs comprise a promising anti-colitis functional food, and this work has established a foundation for future research on these compounds.